Implications of Multiculturalism and Tolerance in Islamic Religious Education - Muh Barid Nizarudin Wajdi; Tobroni Tobroni (STAI Miftahul Ula Nganjuk, 2020)
Education aims to shape attitudes and behaviors towards civilized human beings. An education system that only emphasizes the transfer of knowledge, makes education no longer meaningful and has a positive effect on learners. It is less touching on the humanism side that ultimately develops pluralism as the foundation of multiculturalism. This model of religious education will only create learners to make